Quadratic Equation Help

label Mathematics
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

Calculating (x-3)(x-4) = 0

Nov 19th, 2014

Basically you have to prove that x-3 = 0 and x-4 = 0 

Does x-3 = 0 ? 

(3-3)(3-4) = (0)(-1) = 0 

Does x-4 = 0? 

(4-3)(4-4) = (1)(0) = 0 

Thus, this equation does equate to 0 

Nov 19th, 2014

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Nov 19th, 2014
...
Nov 19th, 2014
Sep 25th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer